Oxidation-resistant segmented copolymer emulsifier nanoparticles and synthesis method thereof

By designing the synthetic nucleus as hydrophobic monomer tBOS and the shell as a diblock copolymer nanoparticle with hydrophilic monomer DMAEMA, the problem of unsaturated lipid compounds being easily oxidized in food and cosmetics is solved, and efficient antioxidant effect and good emulsification performance are achieved.

CN119708391APending Publication Date: 2025-03-28CHANGZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411867788.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Unsaturated lipid compounds added to foods and cosmetics are easily chemically oxidized, resulting in the production of odors and toxic products. The existing natural antioxidants are difficult to spontaneously located at the oil-water interface and cannot effectively prevent lipid oxidation.

Method used

A diblock copolymer nanoparticle with a core of hydrophobic monomer tBOS and a shell of hydrophilic monomer DMAEMA was designed to synthesize a diblock copolymer nanoparticle with different hydrolysis times in the acid, and different contents of phenolic hydroxyl groups were generated, thereby regulating emulsification performance and antioxidant ability.

Benefits of technology

The preparation of antioxidant emulsifier nanoparticles with adjustable morphology has been achieved. The product has good emulsification properties and antioxidant ability, which can effectively prevent lipid oxidation, and is suitable for the pharmaceutical and cosmetic fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708391A_ABST
    Figure CN119708391A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material synthesis, and particularly relates to antioxidant block copolymer emulsifier nanoparticles and a synthesis method thereof. A block A is a hydrophilic polymer, a block B is a hydrophobic polymer, a small molecular reagent containing a trisulfide bond is used as a small molecular chain transfer agent, A-B diblock copolymer nanoparticles containing phenolic hydroxyl groups are synthesized through RAFT-PISA reaction, the block A is a hydrophilic polymer, and the block B is a hydrophobic polymer. The particles are hydrolyzed under certain conditions, polymer protecting groups in the nucleation B block are removed, and the polymer nanoparticles with phenolic hydroxyl groups are obtained and can be further used for free radical removal and oil-water stable interfaces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material synthesis, and particularly relates to antioxidant block copolymer emulsifier particles and a synthesis method thereof. Background Art

[0002] In the field of food and cosmetics, some healthy unsaturated lipid compounds, such as polyunsaturated fatty acids, omega-3 fatty acids, conjugated linoleic acid, etc., are often added to increase food nutrition and improve the texture and performance of food or cosmetics. These unsaturated lipid compounds are mostly hydrophobic compounds and usually need to be added to water-based foods or cosmetics in the form of oil-in-water emulsions. However, bioactive lipid compounds are easily chemically oxidized, resulting in the production of odorous and toxic products and loss of activity. Therefore, research on improving the chemical stability of unsaturated lipid compounds encapsulated in emulsion products is of great significance in both academic and industrial application fields.

[0003] Important components in emulsion products that promote lipid compound oxidation, such as transition metals, enzymes, and photosensitizers, are usually located in the water phase. Therefore, the physicochemical properties of the oil-water interface play a key role in the lipid compound oxidation process. The use of antioxidants is a very effective strategy to prevent lipid compound oxidation in emulsion products, and antioxidants located at the oil-water interface can prevent lipid oxidation better than those located in the water phase or the oil phase.

[0004] However, many naturally occurring food and biocompatible antioxidants do not spontaneously localize at the interface between the two phases. To address this problem, researchers combine emulsifier molecules with antioxidant compounds, usually phenolic compounds, through physical or chemical effects to prepare emulsifiers or co-emulsifiers with antioxidant properties. These emulsifier or co-emulsifier molecules with antioxidant properties are adsorbed on the surface of dispersed droplets to prevent the encapsulated lipid compounds from oxidizing. However, the molecular structure of surface-active antioxidants needs to be precisely controlled to obtain a balance between interfacial emulsification activity and antioxidant properties to achieve optimal performance. Summary of the invention

[0005] In order to realize the preparation of antioxidant emulsifier nanoparticles with adjustable morphology, the present invention designs and synthesizes a diblock polymer nanoparticle whose core is a hydrophobic monomer tBOS (4-tert-butyloxystyrene) and whose shell is a hydrophilic monomer DMAEMA (dimethylaminoethyl methacrylate). The core of the nanoparticle can further generate different contents of phenolic hydroxyl groups by controlling different hydrolysis times in acid, thereby further obtaining emulsifier particles with good emulsification performance and certain antioxidant properties.

[0006] The synthesis steps of the diblock copolymer nanoparticles PDMAEMA-PtBOS are as follows:

[0007] (1) A trisulfide-bonded small molecule chain transfer agent compound I, 4-cyano-4-(dodecylthiothiocarbonyl)thiopentanoic acid (CDPA), has a structure shown in the following chemical formula:

[0008]

[0009] The preparation method of the small molecule chain transfer agent is as follows: n-dodecyl mercaptan is reacted with sodium hydride, carbon disulfide and iodine in a solvent to obtain a reaction mixture; the obtained reaction mixture is then reacted with 4,4'-azobis(4-cyanovaleric acid) in a solvent at a molar ratio of 1.5:1 to obtain 4-cyano-4-(dodecylthiothiocarbonyl)thiopentanoic acid.

[0010] In the process of obtaining the mixture, the molar ratio of n-dodecyl mercaptan: sodium hydride is 76:79, and the molar ratio of carbon disulfide: iodine is 79:25; ether is selected as the solvent to provide a reaction atmosphere, and the mixture is stirred at 0-10°C for 10-20 minutes.

[0011] In the process of obtaining compound I, ethyl acetate was selected as the solvent to provide a reaction atmosphere, and the mixture was heated under reflux at 80° C. for 18 h and washed with water five times.

[0012] (2) The diblock copolymer nanoparticles based on poly (dimethylaminoethyl methacrylate)-b-poly (4-tert-butoxystyrene-co-4-vinylphenol) have the structure shown in the following chemical formula.

[0013]

[0014] In the formula, n is the degree of polymerization of dimethylaminoethyl methacrylate, n is 10-100, preferably 10-50, and x is the degree of polymerization of 4-tert-butoxystyrene-co-4-vinylphenol, x is 50-1000, preferably 100-300.

[0015] The molecular weight distribution coefficient of the diblock copolymer based on poly(dimethylaminoethyl methacrylate)-b-poly(4-tert-butoxystyrene-co-4-vinylphenol) is less than 1.5.

[0016] The preparation method of copolymer nanoparticles is carried out according to the following steps:

[0017] Step 1: using dimethylaminoethyl methacrylate (DMAEMA) as a polymerization monomer to perform reversible addition-fragmentation chain transfer (RAFT) polymerization to obtain a polydimethylaminoethyl methacrylate macromolecular chain transfer agent (i.e., a macromolecule having a dimethylaminoethyl methacrylate repeating unit in the middle and a trithioester bond functional group retained at the end of the chain).

[0018]

[0019] In step 1, under nitrogen conditions, initiator AIBN is added to the solvent for reaction at a temperature of 70° C. for a reaction time of 6 to 8 h to synthesize compound II;

[0020] The molar ratio of dimethylaminoethyl methacrylate to CDPA is 20:1, and the concentration of the dimethylaminoethyl methacrylate solution is 78.6-173 mg / mL, preferably 170 mg / mL; the solvent is toluene, 1,4-dioxane, tetrahydrofuran, etc., preferably toluene.

[0021] The molar ratio of AIBN to CDPA is 1:4.5-5.5, preferably 5;

[0022] Step 2, using the polydimethylaminoethyl methacrylate obtained in step 1 as a macromolecular chain transfer agent and 4-tert-butoxystyrene as a monomer to carry out reversible addition-fragmentation chain transfer dispersion polymerization to obtain polydimethylaminoethyl methacrylate-b-poly 4-tert-butoxystyrene copolymer nanoparticles III.

[0023]

[0024] In step 2, the reaction is carried out under anaerobic conditions, the reaction temperature is 70° C., the initiator is AIBN, the reaction time is 24 to 48 hours, the reaction solvent is methanol / water, ethanol / water, isopropanol / water, and the ratio is 8 / 2 to 10 / 0. The preferred reaction solvent is isopropanol / water, and the preferred ratio is 8 / 2.

[0025] In step 2, the molar ratio of 4-tert-butoxystyrene, poly(dimethylaminoethyl methacrylate) and initiator AIBN is (50-1000):1:(0.5-0.2), preferably (100-300):1:0.2, and the concentration of 4-tert-butoxystyrene in the solvent is 100-170 mg / mL.

[0026] Step 3, diluting the poly(dimethylaminoethyl methacrylate)-b-poly(4-tert-butoxystyrene) polymer nanoparticle compound III obtained in step 2, and hydrolyzing it with acid to obtain poly(dimethylaminoethyl methacrylate)-b-poly(4-tert-butoxystyrene-co-4-vinylphenol) block copolymer nanoparticle IV.

[0027]

[0028] In step 3, the reaction solvent is a mixed solvent of isopropanol / water with a volume ratio of 8 / 2, the concentration of compound III in the mixed solvent of isopropanol and water is 5-10 mg / mL, the acid is hydrochloric acid or trifluoroacetic acid, preferably trifluoroacetic acid, the amount of trifluoroacetic acid is 5-10 times the amount of polymer, preferably 5 times, the reaction time is 24-48 h, and the reaction temperature is 60-85° C., preferably 85° C.

[0029] Beneficial effects:

[0030] The present invention can quickly synthesize polymer nanoparticles having both emulsification properties and free radical scavenging capabilities, and the product has a clear structure, controllable composition, easy separation and purification, and high preparation efficiency and yield. The content of phenolic hydroxyl groups can be regulated by controlling the polymer composition and hydrolysis time, thereby regulating the antioxidant capacity of the polymer nanoparticles.

[0031] The block copolymer nanoparticles prepared by the present invention can be successfully used to prepare antioxidant Pickering emulsions and have application prospects in the fields of medicine, cosmetics, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The compound I synthesized in Example 1 1 H NMR spectrum.

[0033] Figure 2 The compound II synthesized in Example 1 1 H NMR spectrum

[0034] Figure 3 The compound III synthesized in Example 1 1 H NMR spectrum

[0035] Figure 4 This is the GPC chart of compound II synthesized in Example 1.

[0036] Figure 5 This is the GPC chart of compound III synthesized in Example 1.

[0037] Figure 6 This is the TEM image of compound III synthesized in Example 1.

[0038] Figure 7 The compound IV synthesized in Example 1 1 H NMR spectra

[0039] Figure 8 This is the GPC chart of compound V synthesized in Example 2.

[0040] Fig. 9 This is the TEM image of compound V synthesized in Example 2.

[0041] Fig.10 This is the GPC chart of compound VI synthesized in Example 3.

[0042] Fig.11 This is the TEM image of compound VI synthesized in Example 3.

[0043] Fig.12 This is the UV curve of the compound IV synthesized in Example 1 and the ABTS free radical scavenging agent.

[0044] Fig.13 This is a UV curve of the compound IV synthesized in Example 1 and the DPPH free radical scavenging agent.

[0045] Fig.14 This is a Pickering emulsion diagram stabilized by compound IV synthesized in Example 1. DETAILED DESCRIPTION

[0046] The following specific implementation cases are intended to further illustrate the present invention, but these specific implementation cases do not limit the protection scope of the present invention in any way.

[0047] Example 1 Synthesis of Compound I

[0048] At a temperature of 0-10°C, 150 mL of ether, n-dodecyl mercaptan (15.4 g, 76 mmol), and sodium hydride (3.15 g, 79 mmol) were added to a 250 mL round-bottom flask, and the mixture was stirred vigorously. When a white slurry of sodium dodecyl trithiocarbonate (14.6 g, 0.049 mol) was observed, carbon disulfide (6 g, 79 mmol) and solid iodine (6.3 g, 0.025 mol) were added and stirred to mix evenly. The reaction mixture was then stirred at room temperature for 1 hour, and the precipitated white sodium iodide was removed by filtration. The yellow-brown filtrate was washed with an aqueous sodium thiosulfate solution to remove excess iodine and water, dried with sodium sulfate and evaporated to obtain residual bis-(dodecylthiothiocarbonyl) disulfide. 4,4'-azobis(4-cyanovaleric acid) (2.10 g, 0.0075 mol) and the above-mentioned bis-(dodecylthiocarbonylthio) disulfide (2.77 g, 0.005 mol) were heated to 80°C and refluxed in ethyl acetate (50 mL) for 18 hours. After removing the volatiles in vacuo, the crude product was washed with deionized water (5×100 mL), saturated sodium carbonate solution (3×100 mL), and saturated brine (3×100 mL), respectively, and finally recrystallized from n-hexane to obtain 4-cyano-4-(dodecylthiocarbonylthio)pentanoic acid as a light yellow solid CDPA.

[0049] Synthesis of compound II

[0050] Add dimethylaminoethyl methacrylate (3.71g, 20mmol), CDPA (40.3mg, 1mmol), AIBN (32.84mg, 0.2mmol), and toluene (21.3mL) into a 25mL Schlenk flask. After three cycles of liquid nitrogen freezing-nitrogen blowing-oxygen exhaust, seal the flask and transfer it to a 70°C oil bath. After 7.5h of polymerization, quench with liquid nitrogen to stop the reaction. Then slowly add the reaction mixture dropwise into a large amount of cold n-hexane to settle, and finally dry it in a vacuum drying oven at 45°C for 24h to obtain a yellow colloid. The yield calculated by weighing is: 3.6g (97%). GPC (THF): Mn = 3516g / mol,

[0051] Synthesis of Compound III

[0052] 4-tert-Butoxystyrene (0.1763 g, 1 mmol), compound II (40 mg, 0.01 mmol), AIBN (0.3284 mg, 0.002 mmol), isopropanol / water (the ratio of the two is 8 / 2) (0.88 g) were added to a 25 mL Schlenk flask. After three cycles of liquid nitrogen freezing-nitrogen blowing-oxygen exhaust, the flask was sealed and transferred to a 70°C oil bath. After 24 hours of polymerization, the reaction was quenched with liquid nitrogen to stop the reaction. The reaction mixture was then slowly added dropwise to a large amount of cold methanol to settle, and finally dried in a vacuum drying oven at 45°C for 24 hours to obtain a white powder. The yield was calculated by weighing: 0.23 g (66%). GPC (THF): Mn = 12665 ​​g / mol,

[0053] Synthesis of Compound IV

[0054] Trifluoroacetic acid (5.34 mg, 0.047 mmol) was added to a 25 mL round-bottom flask, and compound III

[0055] (528.78 mg, 0.009 mmol), after nitrogen bubbling and oxygen removal, the flask was sealed and transferred to an oil bath at 85°C. After 24 hours of polymerization, the reaction was quenched with liquid nitrogen to stop the reaction. The reaction mixture was then centrifuged and washed five times, dissolved in tetrahydrofuran, and added dropwise to a 10-fold volume of a mixed solvent of methanol / water (volume ratio of 3 / 7), the precipitate was collected, and finally dried in a vacuum drying oven at 45°C for 24 hours to obtain a white powder, the yield of which was calculated by weighing: 0.23 g (66%).

[0056] Example 2

[0057] Synthesis of Compound Ⅴ

[0058] 4-tert-Butoxystyrene (0.3525 g, 2 mmol), compound II (40 mg, 0.01 mmol), AIBN (0.3284 mg, 0.002 mmol), isopropanol / water (the ratio of the two is 8 / 2) (1.7626 g) were added to a 25 mL Schlenk bottle. After three cycles of liquid nitrogen freezing-nitrogen blowing-oxygen exhaust, the flask was sealed and transferred to a 70°C oil bath. After 24 hours of polymerization, the reaction was quenched with liquid nitrogen to stop the reaction. The reaction mixture was then slowly added dropwise to a large amount of cold methanol to settle, and finally dried in a vacuum drying oven at 45°C for 24 hours to obtain a white powder. The yield was calculated by weighing: 0.25 g (70%). GPC (THF): Mn = 15088 g / mol,

[0059] Example 3

[0060] Synthesis of Compound VI

[0061] 4-tert-Butoxystyrene (0.5288 g, 3 mmol), compound II (40 mg, 0.01 mmol), AIBN (0.3284 mg, 0.002 mmol), isopropanol / water (the ratio of the two is 8 / 2) (2.64 g) were added to a 25 mL Schlenk flask. After three cycles of liquid nitrogen freezing-nitrogen blowing-oxygen exhaust, the flask was sealed and transferred to a 70°C oil bath. After 24 hours of polymerization, the reaction was quenched with liquid nitrogen to stop the reaction. The reaction mixture was then slowly added dropwise to a large amount of cold methanol for precipitation, and finally dried in a vacuum oven at 45°C for 24 hours to obtain a white powder. The yield was calculated by weighing: 0.23 g (66%). GPC (THF): Mn = 17523 g / mol,

Claims

1. An antioxidant block copolymer emulsifier nanoparticle, characterized in that: The structure of the block copolymer nanoparticles is shown below: In the formula, n is 10 to 100, and x is 50 to 1000.

2. A method for synthesizing antioxidant block copolymer emulsifier nanoparticles as claimed in claim 1, characterized in that: The synthesis method steps are as follows: (1) reacting n-dodecyl mercaptan with sodium hydride, carbon disulfide and iodine in a solvent to obtain a mixture; the mixture is then heated to reflux in a solvent and then recrystallized to obtain a small molecule chain transfer agent compound I: 4-cyano-4-(dodecylthiothiocarbonyl)thiopentanoic acid CDPA; (2) dimethylaminoethyl methacrylate and compound I are reacted in a solvent with initiator AIBN under anhydrous and oxygen-free conditions to synthesize compound II; (3) Compound II is then reacted with 4-tert-butoxystyrene in a solvent and initiator AIBN is added under anaerobic conditions to synthesize compound III; (3) Compound III is then reacted with an acid in an isopropanol / water mixed solvent to generate the target compound IV 3. The method for synthesizing antioxidant block copolymer emulsifier nanoparticles according to claim 2, characterized in that: In step (1), during the reaction to obtain the mixture, the molar ratio of n-dodecyl mercaptan to sodium hydride, carbon disulfide and iodine is 76:79:79:25, the solvent is ether, and the reaction conditions are: stirring at 0-10°C for 10-20 minutes.

4. The method for synthesizing antioxidant block copolymer emulsifier nanoparticles according to claim 2, characterized in that: In step (1), in the process of obtaining compound I, the molar ratio of the reaction mixture to 4,4'-azobis(4-cyanovaleric acid) is 1.5:1, ethyl acetate is selected as the solvent, and the mixture is heated to reflux at 80°C for 18 hours.

5. The method for synthesizing antioxidant block copolymer emulsifier nanoparticles according to claim 2, characterized in that: In step (2), the molar ratio of dimethylaminoethyl methacrylate to CDPA is 20:1, the solvent is toluene, 1,4-dioxane or tetrahydrofuran, and the concentration of dimethylaminoethyl methacrylate in the solvent is 78.6-173 mg / mL; the molar ratio of AIBN to CDPA is 1:4.5-5.5; the reaction temperature is 70°C, and the reaction time is 6-8 hours.

6. The method for synthesizing antioxidant block copolymer emulsifier nanoparticles according to claim 2, characterized in that: In step (3), the molar ratio of 4-tert-butoxystyrene, poly(dimethylaminoethyl methacrylate) and initiator AIBN is 50-1000:1:0.5-0.2, the solvent is methanol / water, ethanol / water or isopropanol / water in a volume ratio of 8 / 2-10 / 0, and the concentration of 4-tert-butoxystyrene in the solvent is 100-170 mg / mL.

7. The method for synthesizing antioxidant block copolymer emulsifier nanoparticles according to claim 2, characterized in that: In step (4), the reaction temperature of compound III and acid is 60-85° C., and the reaction time is 24-48 h; the acid is hydrochloric acid or trifluoroacetic acid, the concentration of compound III in a mixed solvent of isopropanol and water is 5-10 mg / mL, and the volume ratio of isopropanol to water is 8 / 2.

8. The use of the antioxidant block copolymer emulsifier nanoparticles according to claim 1, characterized in that: The block copolymer nanoparticles containing phenolic hydroxyl groups can be used to stabilize the oil-water interface and slow down the oxidation of active substances in the oil phase of the Pickering emulsion.

Citation Information

Patent Citations

  • High-performance PE film as well as preparation method and application thereof

    CN113635636A

  • Resist material and pattern forming method using the same

    JP2011039315A

  • Cosmetic composition containing an amphiphilic zwitterionic copolymer

    US20110300093A1

  • Block polymer including isobutyl acrylate and acrylic acid, cosmetic composition and treatment method

    US20140105838A1